Predictors of Postoperative Cognitive Decline in Very Old Patients With Hip Fracture: A Retrospective Analysis. (December 2014) - Luger, Markus F.; Müller, Stephan; Kammerlander, Christian; Gosch, Markus; Luger, Thomas J.
Background: To investigate incidence and predictors of the various postoperative cognitive declines in old patients with hip fracture. Methods: This retrospective chart study evaluated 411 patients (age ≥80 years, follow-up 5 years). After exclusion of 82 patients (preexisting dementia or delirium), 70 patients showing either diagnosed postoperative delirium (POD; group 1; N = 18, 5.5%) or an unspecified cognitive dysfunction and behavior (group 2; N = 52, 15.8%) were analyzed and compared with those without any acute postoperative cerebral impairment (control group; N = 259, 78.7%). Medical history, anesthesiological, orthopedic, and rehabilitation data were assessed using the medical database of the hospital information system. Relative ratio was calculated with Fisher exact test: P value Bonferroni corrected ≤.003. Results: Acute cognitive complications were observed in 70 (21.3%) patients. Our data in group 1 showed that patients with a medical history of stroke (relative risk [RR] = 16.2, P = .0001) or nicotine abuse (RR = 14.4, P = .001) and perioperative surgical bleeding (RR = 6.54, P = .002) are more likely to develop POD. Unspecified cognitive dysfunction and behavior (group 2) was significantly associated with a medical history of stroke (RR = 12.5, P = .0001) and postoperatively with depression (RR = 3.32, P = .001). In the follow-up, significantly more patients in group 1 (55.6%, RR = 21.8, P = .0001) and group 2 (13.5%, RR = 3.88, P = .001) developed dementia as compared to controls (1.9%). Mortality did not differ significantly between the groups (group 1: RR = 1.75, P = .5 and group 2: RR = 0.66, P = 1.0). Conclusion: These data show that various predictors can identify a greater likelihood of developing postoperative cognitive decline in very old patients with hip fracture. Not identifying or labeling of POD limits the opportunity for evaluation, treatment, and planning. Thus, routine cognitive assessments need to be performed in the scope of multidisciplinary orthogeriatric comanagement.